Earnings management and annual report readability - Lo, Kin; Ramos, Felipe; Rogo, Rafael (Journal of Accounting and Economics, 2017)
We explore how the readability of annual reports varies with earnings management. Using the Fog Index to measure readability (Li, 2008), and focusing on the management discussion and analysis section of the annual report (MD&A), we predict and find that firms most likely to have managed earnings to beat the prior year's earnings have MD&As that are more complex. This disruption of the overall pattern of readability increasing with the level of earnings found in Li (2008) challenges the ontological explanation that good news is inherently easier to communicate, and shows that obfuscation contributes to making disclosures more complex.